2021
DOI: 10.1186/s12931-021-01744-6
|View full text |Cite|
|
Sign up to set email alerts
|

The modification effect of temperature on the relationship between air pollutants and daily incidence of influenza in Ningbo, China

Abstract: Background Although exposure to air pollution has been linked to many health issues, few studies have quantified the modification effect of temperature on the relationship between air pollutants and daily incidence of influenza in Ningbo, China. Methods The data of daily incidence of influenza and the relevant meteorological data and air pollution data in Ningbo from 2014 to 2017 were retrieved. Low, medium and high temperature layers were stratifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
(70 reference statements)
0
11
0
2
Order By: Relevance
“…It was also found that PM10 and temperature are associated with pediatric cases of infections by the influenza A virus. Both factors can synergize in children’s respiratory tract, resulting in increased infection susceptibility by the influenza virus (Xu et al 2013 ; Zhang et al 2021 ).
Fig.
…”
Section: Particulate Mattermentioning
confidence: 99%
“…It was also found that PM10 and temperature are associated with pediatric cases of infections by the influenza A virus. Both factors can synergize in children’s respiratory tract, resulting in increased infection susceptibility by the influenza virus (Xu et al 2013 ; Zhang et al 2021 ).
Fig.
…”
Section: Particulate Mattermentioning
confidence: 99%
“…The effects of atmospheric pollutants and meteorological factors on human health are of great concern. Extreme weather and various atmospheric pollutants may contribute to the onset of measles ( 24 ), influenza ( 25 27 ), tuberculosis ( 28 ), COVID-19 ( 29 , 30 ), and HFMD ( 8 , 31 ) among other infectious diseases. HFMD has caused multiple outbreaks and millions of illnesses globally and is emerging as a pressing global public health issue ( 4 ), resulting in a significant disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…Through the cluster detection with the spatial scan statistics method, we found that (1) each of the three diseases has abnormally high-risk areas in mainland China; (2) the first clusters of three common diseases in the three study years are mostly located in the southern and southeastern coastal areas, and in 2014–2015, their first clusters had an overlap in south coastal areas; (3) the first cluster of influenza shows the most drastic dynamic during the 3 years, moving from North China to the southeast coast. This last finding is new, because previous studies of clusters of influenza in China have been either about a local region or about one time period [ 15 , 41 , 42 ], and therefore not able to identify the dynamic on a national scale. The clusters of DF we identified are mostly related to the outbreaks in Guangdong province in 2014, which confirmed the findings of previous studies [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 98%